POLITICAL ECONOMY ANALYSIS IN NON-COMPLIANCE INDONESIA TOWARDS FRAMEWORK CONVENTION ON TOBACCO CONTROL - Hijra Nasir (Jurnal PIR : Power in International Relations, 2020)
This research attempts to analyze the reason or consideration of Indonesian government to not ratify Framework Convention on Tobacco Control (FCTC) yet, in political economy analysis comprises interest of many actors, limitations of capacity of state, the influence of ratification towards Indonesian tobacco trade, FCTC implementation among the Parties, and projection of Indonesia’s possibility to comply with this regulation. FCTC has a number of instruments in tobacco control which was arranged by World Health Organization since 1999. This research become necessary due to Indonesia as only one a country in Asia which have not ratified yet, whereas Indonesia has been the fifth biggest of tobacco consumer in the world. It is a qualitative research, where data were collected through interview technique to the certain sources, and other supporting data from books and publication document. It has been analyzed using Chayes concept about compliance and non-compliance with international regulatory agreement consist of ambiguity and lack of capacity, interests, norms, and efficiency. In observing this issue, we can clarify that different interests of actors have become major consideration of Indonesian government to not comply with this convention regarding on the differences priority within ministry, the existence of business actors to influence the decision maker, employment, tobacco farmers, and social cultural aspects. In the forthcoming, there is a possibility that Indonesia will ratify FCTC due to Tobacco Roadmap which is arranged by Ministry of Industry of Indonesia in long-term planning assert that health aspect will be the main priority more than state revenues and employment. In addition, there are a lot of regencies and cities in Indonesia which have been implementing tobacco control regulation. This research, eventually, is expected to provide input analysis to the government in accordance with FCTC.